Minimal intervention in dentistry: Which is the best approach for silorane composite restoration repairs? - Zanatta, Rayssa-Ferreira [UNESP]; Torres, Carlos-Rocha-Gomes [UNESP]; de Oliveira, Juliana-Boa-Sorte [UNESP]; Yui, Karen-Cristina-Kazue [UNESP]; Matuda, Amanda-Guedes-Nogueira [UNESP]; Lopes, Stephanie-Ribeiro [UNESP]; Mafetano, Ana-Paula-Valente-Pinho [UNESP]; Campos, Raquel-Pinto [UNESP]; Borges, Alessandra-Bühler [UNESP]; Pucci, Cesar-Rogério [UNESP] (Medicina Oral, S.L., 2021)
Background: This study aimed to evaluate surface treatments, adhesives and composites for repairing silorane based restorations. Material and Methods: One hundred and twenty truncated cones (2 mm smaller diameter and 4 mm larger diameter) made of silorane composite were divided in 12 groups according with the surface treatment (diamond bur and oxide aluminum abrasion), the adhesive (Adper Scothbond Multipurpose (3M ESPE), Ecusit (Voco) and Filtek P90 Adhesive (3M ESPE)). Each group was subdivided in two according with the composite used for repair (methacrylate and silorane). The repair was made with a second truncated cone build over the first one and bond strength assssed by tensile strength. Data were submitted to ANOVA 3-way and Tukey’s test (p<0.05). Results: There was difference only for the adhesives and the composites, with conventional adhesives (Adper Scothbond Mutipurpose) and methacrylate-based composites (Filtek Z350) presenting superior tensile strength compared to the silorane ones (P90 Adhesive system and composite). Conclusions: Therefore, it must be concluded that silorane composite can be repaired with methacrylate base composites and adhesives.
Keywords: bond strength; composites; minimal intervention; Silorane composites